Developing problem-based learning modules for flat-sided geometry to facilitate students' mathematical connection skills - Ali, Elsiska Ningsi; Armis; Saragih, Sehatta (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2024)
This development study aims to produce a problem-based learning module on flat-sided geometry designed to enhance students' mathematical connection skills in Phase D. The teaching module consists of three main sections: the core, general information, and appendices. Given the limitations in students' mathematical connection skills, it is essential for teachers to use effective learning models. Problem-based learning focuses on real-world problems as the central point of instruction, helping students connect lessons to practical, everyday situations. This study followed the 4D development model, which includes the stages of define, design, develop, and disseminate. Product validation was conducted by three validators, who provided feedback for improvements. The readability of the student worksheets was tested through one-on-one trials with three students. Additionally, small-group trials involving 15 Phase D students from MTsN 4 Kampar were conducted to assess the module's practicality. The validation results showed an average score of 3.58, indicating the module is highly valid. The practicality test resulted in an average score of 87.5%, classifying the module as very practical. These findings demonstrate that the developed module can effectively improve students' mathematical connection skills. Furthermore, teachers can use this product as a teaching tool for the flat-sided geometry material in the mathematics learning process.